Scanning tunneling microscopy on cleaved Mn(3)Sn(0001) surface - Yang, Hung-Hsiang (Sci Rep, 2019)
We have studied in-situ cleaved (0001) surfaces of the magnetic Weyl semimetal Mn(3)Sn by low-temperature scanning tunneling microscopy and spectroscopy (STM/S). It was found that freshly cleaved Mn(3)Sn surfaces are covered with unknown clusters, and the application of voltage pulses in the tunneling condition was needed to achieve atomically flat surfaces. STM topographs taken on the flat terrace show a bulk-terminated 1 × 1 honeycomb lattice with the Sn site brightest. First-principles calculations reveal that the brightest contrast at the Sn site originates from the surrounding surface Mn d orbitals. Tunneling spectroscopy performed on the as-cleaved and voltage-pulsed surfaces show a prominent semimetal valley near the Fermi energy.